Notch Signalling in Breast Development and Cancer - Edwards, Abigail; Brennan, Keith (Frontiers in Cell and Developmental Biology, 2021)
The Notch signalling pathway is a highly conserved developmental signalling pathway, with vital roles in determining cell fate during embryonic development and tissue homeostasis. Aberrant Notch signalling has been implicated in many disease pathologies, including cancer. In this review, we will outline the mechanism and regulation of the Notch signalling pathway. We will also outline the role Notch signalling plays in normal mammary gland development and how Notch signalling is implicated in breast cancer tumorigenesis and progression. We will cover how Notch signalling controls several different hallmarks of cancer within epithelial cells with sections focussed on its roles in proliferation, apoptosis, invasion, and metastasis. We will provide evidence for Notch signalling in the breast cancer stem cell phenotype, which also has implications for therapy resistance and disease relapse in breast cancer patients. Finally, we will summarise the developments in therapeutic targeting of Notch signalling, and the pros and cons of this approach for the treatment of breast cancer.